Efficient and stable electrode material and preparation method thereof
By electrodepositing a porous layered nickel hydroxide electrode on the nickel mesh and using ionic embedding and sintering steps to form a highly catalytically active shell, the problems of high cost of precious metal catalysts and reduced Ni(OH)2 activity in traditional electrolytic water technology are solved, and efficient and stable electrode materials are achieved.
Patent Information
- Application Number
- CN202411962174.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
Traditional electrolytic technology uses precious metal catalysts, which are costly and scarce, and the activity of simple Ni(OH)2 decreases and structurally unstable during long-term electrolysis.
A porous layered nickel hydroxide electrode is formed by electrodeposition on the nickel mesh substrate and an ionic embedding and sintering step is employed to form a highly catalytically active shell with a heterostructure.
The catalytic activity and stability of the electrode are improved, structural stability is enhanced, the dissolution and precipitation of active substances are reduced, and the efficiency of electrolytic water reaction is improved.
Smart Images

Figure CN119776891A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a highly efficient and stable electrode material and a preparation method thereof. Background Art
[0002] Water electrolysis can decompose water into hydrogen and oxygen without generating any other pollution, and has important application value in the field of renewable energy. As a clean energy, hydrogen energy is of decisive significance for achieving energy structure transformation and alleviating environmental problems. However, the efficiency of water electrolysis depends largely on the catalytic activity of electrode materials, especially the performance of catalysts in redox reactions.
[0003] Traditional water electrolysis technology generally uses precious metals such as platinum (Pt) and iridium (Ir) as catalysts. Although they show efficient catalytic performance, their high cost and scarce resources limit their widespread application. Therefore, the development of a low-cost and efficient non-precious metal catalyst has become a research hotspot. Nickel-based catalysts are considered to be a very promising choice due to their good catalytic performance, abundant resources and low cost.
[0004] In recent years, layered nickel hydroxide (Ni(OH)2) has been widely studied as an electrode material due to its excellent electrochemical performance and stability. However, pure Ni(OH)2 still faces the challenges of decreased activity and structural instability during long-term electrolysis. Summary of the invention
[0005] The purpose of the present invention is to provide an efficient and stable electrode material and a preparation method thereof in order to overcome the defects of the above-mentioned prior art, and to optimize the electrode catalytic performance and stability through ion embedding and sintering steps. The method is suitable for preparing electrodes for efficient water electrolysis reaction, wherein the porous structure promotes rapid gas discharge and increases the active surface area, while the ions embedded on the surface are used to form a shell with high catalytic activity.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing an efficient and stable electrode material, comprising the following steps:
[0008] S1: pre-treating the nickel mesh substrate to remove surface impurities;
[0009] S2: preparing an electroplating solution containing a nickel source and a pore former, and adjusting the pH value thereof to a range suitable for depositing layered nickel hydroxide;
[0010] S3: using the pretreated substrate as a cathode, generating a layered nickel hydroxide layer on the substrate surface by electrodeposition;
[0011] S4: using an ion embedding method to allow ions to enter the layered nickel hydroxide layer, wherein the ion embedding method includes an immersion embedding method or an electrochemical embedding method;
[0012] S5: The ion-embedded material is sintered in a nitrogen atmosphere, and after cooling, post-processed to obtain a highly efficient and stable electrode material.
[0013] Furthermore, in S1, the pretreatment step includes ultrasonic cleaning in dilute hydrochloric acid, deionized water and anhydrous ethanol in sequence, and then natural drying.
[0014] Furthermore, in S2, the nickel source is one of nickel sulfate, nickel nitrate, and nickel chloride, the pore-forming agent is ammonium chloride, the concentration of nickel sulfate in the electroplating solution is 0.1M to 1M, the concentration of ammonium chloride in the electroplating solution is 0.5M to 4M, and the pH value of the electroplating solution is adjusted to 10 to 12.
[0015] Furthermore, in S3, during the electrodeposition process, the current density was 0.1 A / cm 2 ~2A / cm 2 The electrodeposition time is 5 to 30 minutes and the temperature is 20°C to 60°C.
[0016] Further, in S4, the immersion embedding method comprises the following steps:
[0017] Select an ion source and prepare a soaking solution with a concentration of 0.01M to 0.1M, and adjust the pH value of the solution;
[0018] The electrode after electrodeposition is completely immersed in the soaking solution, and the soaking time is controlled to be 0.1 to 100 hours under stirring conditions, and the temperature is room temperature to 80° C.;
[0019] After soaking, take out the electrode, rinse it with deionized water and dry it naturally.
[0020] Further, in S4, the electrochemical embedding method comprises:
[0021] Select an ion source and prepare an electrolyte with a concentration of 0.01M to 0.1M, and adjust the pH value of the solution;
[0022] The electrode after electrodeposition is completely immersed in the electrolyte, and a circulating current is applied to perform electrochemical cycling, wherein the cycle time is 10 min to 90 min, the number of cycles is 10 to 100 times, and the temperature is room temperature to 80° C.;
[0023] After the cycle was completed, the electrode was removed, rinsed with deionized water and dried naturally.
[0024] Furthermore, in S4, the pH of the solution is adjusted to avoid precipitation or decomposition of ions.
[0025] Furthermore, in S5, the sintering temperature is 500°C to 1000°C, the sintering time is 3 to 12 hours, and the heating rate and cooling rate during sintering are both 5°C / min.
[0026] Furthermore, in S4, during the ion embedding process, the ions include one or more of lanthanum ions, cobalt ions, and iron ions.
[0027] The second aspect of the present invention provides a method for preparing a highly efficient and stable electrode material obtained by the above-mentioned preparation method.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] Compared with the traditional electrode preparation method, the innovation of this method lies in the formation of a porous nickel hydroxide electrode on the surface of a nickel substrate through electrodeposition and subsequent processing steps, and the introduction of an embedding process of catalytically active ions. This innovative strategy changes the structure of layered nickel hydroxide, thereby forming a material with a heterogeneous structure on the electrode surface. Through ion embedding, the crystal structure and surface chemical properties of nickel hydroxide are regulated, giving it higher catalytic activity and stability. In the subsequent high-temperature sintering process, a stable and highly active heterogeneous structure is formed on the surface of the porous electrode. This sintering process not only further enhances the structural stability of the electrode, reduces the dissolution and precipitation of active substances, but also helps to improve the catalytic activity of the electrode. This makes this method have important application prospects and value in the field of electrocatalytic material preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an electron microscope image of a porous electrode with nickel hydroxide loaded on its surface;
[0031] Figure 2 The SEM and EDS images of the electrode after La ion embedding;
[0032] Figure 3 The SEM and EDS images of the electrode after sintering after La ions are embedded;
[0033] Figure 4 TEM image of the electrode after sintering after La ion embedding;
[0034] Figure 5 This is the performance curve of the electrode. DETAILED DESCRIPTION
[0035] In order to overcome these limitations in the prior art, the present invention proposes an innovative method, namely, preparing Ni(OH)2 on a nickel mesh by electrodeposition technology, and then forming an electrode with a heterogeneous structure shell by introducing different ions and sintering. This structure can significantly improve the catalytic activity and stability of the electrode.
[0036] Therefore, the background of the present invention is based on seeking to develop a new type of efficient and stable nickel-based electrode material, which can overcome the limitations of the prior art, provide higher water electrolysis efficiency and longer service life, and thus promote the sustainable development of hydrogen energy.
[0037] The innovation of the technical solution of the present invention lies in that, through the ion embedding and sintering process, not only the electrochemical performance of Ni(OH)2 is improved, but also a heterogeneous structure is introduced, which can provide more active sites, improve the charge transfer efficiency, and enhance the structural stability of the material. This method is expected to greatly improve the performance of electrode materials, achieve a more efficient and stable water electrolysis process, and thus provide key technical support for the efficient production of hydrogen energy.
[0038] In specific implementation, the present invention provides a method for preparing a porous self-supporting electrode with layered nickel hydroxide (Ni(OH)2) on the surface, and optimizes the electrode catalytic performance and stability through ion embedding and sintering steps. The method is suitable for preparing electrodes for efficient water electrolysis reactions, wherein the porous structure promotes rapid gas discharge and increases the active surface area, while the surface embedded ions are used to form a shell with high catalytic activity.
[0039] 1. Preparation of porous electrodes loaded with nickel hydroxide
[0040] A) Substrate pretreatment
[0041] The nickel mesh substrate was ultrasonically cleaned in dilute hydrochloric acid for 15 minutes to remove the surface oxide layer and possible metal impurities;
[0042] Then ultrasonically clean it in deionized water for 15 minutes to remove surface impurities and residual hydrochloric acid;
[0043] Then, ultrasonic cleaning was performed in anhydrous ethanol for 15 minutes to remove impurities such as organic matter on the surface;
[0044] Finally let it dry naturally.
[0045] B) Preparation and adjustment of plating solution
[0046] Prepare the electroplating solution: prepare a mixed solution containing nickel salt: [nickel sulfate (NiSO4) or nickel nitrate (Ni(NO3)2) or nickel chloride (NiCl2)] and pore former [ammonium chloride (NH4Cl)].
[0047] Among them, nickel salt serves as a nickel source; ammonium chloride decomposes to produce hydrogen during the electrolysis process, which helps to form a bubble template.
[0048] The concentration of nickel sulfate is 0.1M to 1M, and the concentration of ammonium chloride is 0.5M to 4M.
[0049] pH adjustment: Add an appropriate amount of sodium hydroxide (NH4OH) to the plating solution and adjust the pH value to about 10-12 to ensure the stable formation of surface layered nickel hydroxide during the deposition process.
[0050] C) Electrodeposition Process
[0051] Electrode setting: Use the pretreated nickel mesh as the cathode and connect it to the negative power supply; use the titanium basket filled with nickel particles as the anode and connect it to the positive power supply.
[0052] Electrodeposition parameters: Electrodeposition is performed by applying a constant current density through a power supply, and the current density can be 0.1A / cm 2 ~2A / cm 2 The electrodeposition time is controlled within 5 to 30 minutes, and the temperature is controlled within 20°C to 60°C to ensure that a layered nickel hydroxide layer is formed on the surface of the porous electrode.
[0053] D) Post-processing
[0054] After the electrodeposition was completed, the electrode was taken out from the electrolyte, rinsed with deionized water to remove the residual electrolyte on the surface, and then dried naturally at room temperature.
[0055] 2. Ion embedding process
[0056] Method 1: Immersion embedding method (concentration driven)
[0057] A) Preparation of soaking solution
[0058] Select ion source:
[0059] According to the type of ions to be introduced, a suitable chemical reagent is selected, such as lanthanum chloride (LaCl3) as a lanthanum ion source. If multiple ions need to be introduced at the same time, other salts such as cobalt nitrate (Co(NO3)2) or ferric chloride (FeCl3) can be added.
[0060] Preparation of soaking solution:
[0061] Dissolve an appropriate amount of ion source in distilled or deionized water, usually with a concentration of 0.01M to 0.1M, to ensure that the ions are fully present in the solution.
[0062] Adjust the pH of the solution: If the ions are acid or alkaline sensitive, it is necessary to ensure that the pH of the solution is moderate to avoid precipitation or decomposition of the ions.
[0063] B) Soaking process
[0064] Soaking condition settings:
[0065] Completely immerse the electrodeposited porous nickel hydroxide electrode in the ion solution. Ensure that the electrode surface is in full contact with the solution so that the ions can be evenly embedded in the porous structure. At the same time, the solution is continuously stirred to ensure uniform contact and reaction between the solution and the electrode.
[0066] Control soaking time:
[0067] The soaking time may be 0.1 to 100 hours, depending on the desired degree of ion intercalation and the specific application of the electrode.
[0068] Temperature Control:
[0069] The immersion treatment is performed at room temperature, or under temperature-controlled conditions, such as 20-80° C., to accelerate the ion exchange process and improve the ion embedding efficiency.
[0070] C) Post-processing
[0071] Rinse: After soaking, remove the electrode and rinse with plenty of deionized water to remove unreacted ions and possible surface residues.
[0072] Drying: Dry naturally at room temperature, ensuring all moisture is removed without damaging the porous structure.
[0073] Method 2: Electrochemical embedding method (potential driven)
[0074] A) Electrolyte Preparation
[0075] Select ion source:
[0076] According to the type of ions to be introduced, a suitable chemical reagent is selected, such as lanthanum chloride (LaCl3) as a lanthanum ion source. If multiple ions need to be introduced at the same time, other salts such as cobalt nitrate (Co(NO3)2) or ferric chloride (FeCl3) can be added.
[0077] Preparation of soaking solution:
[0078] Dissolve an appropriate amount of ion source in distilled or deionized water, usually with a concentration of 0.01M to 0.1M, to ensure that the ions are fully present in the solution.
[0079] Adjust the pH of the solution: If the ions are acid or alkaline sensitive, it is necessary to ensure that the pH of the solution is moderate to avoid precipitation or decomposition of the ions.
[0080] B) Electrochemical Cycle
[0081] The electrodeposited porous nickel hydroxide electrode is completely immersed in the ion solution to ensure that the electrode surface is in full contact with the solution.
[0082] A circulating current is applied to the electrodes to cause them to undergo electrochemical circulation in the above electrolyte.
[0083] The cycle time and number vary according to the type and size of the embedded ions, and can generally be 10 minutes to 90 minutes, or 10 to 100 electrochemical cycles.
[0084] The temperature of the electrochemical cycle can be room temperature, or can be carried out under temperature-controlled conditions, such as 20-80° C., to accelerate the ion exchange process and improve the ion insertion efficiency.
[0085] C) Post-processing
[0086] Rinse: After soaking, remove the electrode and rinse with plenty of deionized water to remove unreacted ions and possible surface residues.
[0087] Drying: Dry naturally at room temperature, ensuring all moisture is removed without damaging the porous structure.
[0088] 3. Sintering process
[0089] A) Preparation before sintering:
[0090] Make sure the treated material is completely dry.
[0091] Before sintering, the samples were weighed and their masses were recorded in order to evaluate the mass changes during sintering.
[0092] B) Sintering temperature and time:
[0093] The treated material is placed in a tube furnace or a muffle furnace for sintering.
[0094] The sintering temperature is set between 500°C and 1000°C.
[0095] The sintering time is controlled between 3 and 12 hours.
[0096] Heating and cooling rates:
[0097] The heating rate is controlled at 5°C / min to prevent the material from cracking or being damaged due to rapid temperature changes.
[0098] The cooling rate is also controlled, usually set at 5°C / min, to ensure that the material cools slowly and avoid thermal stress caused by rapid cooling.
[0099] C) Atmosphere Control:
[0100] The entire sintering process is carried out in a nitrogen atmosphere to prevent oxidation
[0101] D) Cooling and post-processing:
[0102] After sintering, the samples were allowed to cool naturally to room temperature in the furnace to maintain their structural integrity and stability.
[0103] The cooled samples were washed to remove any surface residues and then dried again.
[0104] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. Any features such as preparation means, materials, structures or composition ratios not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.
[0105] Example 1
[0106] Step 1: Substrate Preparation
[0107] A) The nickel mesh substrate was ultrasonically cleaned in deionized water, 1M dilute hydrochloric acid, and anhydrous ethanol for 15 minutes to remove surface impurities.
[0108] B) The cleaned nickel mesh substrate is placed at the working electrode position and waits for further processing.
[0109] Step 2: Electrodeposition of Porous Nickel Hydroxide Electrode
[0110] A) An electrodeposition solution containing 0.1 M NiSO4, 2 M NH4Cl and 0.1 M NaOH was prepared in an electrodeposition tank, and then the solution was thoroughly mixed by nitrogen aeration.
[0111] B) A clean nickel mesh substrate was placed in an electrodeposition bath and used as a working electrode.
[0112] C) Apply 1A / cm 2 The current density was 2.50 and the electrodeposition was continued for 8 minutes to form a porous nickel hydroxide electrode.
[0113] D) Remove the electrode, rinse with deionized water and dry.
[0114] The porous electrode with nickel hydroxide on the surface is Figure 1 As shown in Figure 1, the layered nickel hydroxide (Ni(OH)2) generated on the surface of the porous electrode.
[0115] Step 3: Lanthanum ion immersion embedding
[0116] A) Prepare a solution containing 0.05 M LaCl3 and disperse it thoroughly by ultrasound.
[0117] B) Immerse the electrode completely in the LaCl3 solution and keep soaking for 12 hours with continuous stirring at room temperature.
[0118] C) Take out the electrode, rinse it with deionized water and dry it under nitrogen atmosphere for the next step.
[0119] The SEM and EDS images of the electrode after La ion embedding are shown in Figure 2. Figure 2 As shown, 1 is the SEM image of the electrode after La ions are embedded, 2 is the distribution of Ni elements in the EDS image, and 3 is the distribution of La elements in the EDS image. It can be seen that La ions are uniformly embedded in the layered sodium hydroxide on the surface of the electrode.
[0120] Step 4: Sintering:
[0121] A) Heat treatment before sintering:
[0122] The samples were preheated to 200 °C in a tube furnace for 1 h to remove any organic matter or moisture that might be present.
[0123] B) Sintering temperature and duration:
[0124] The temperature of the preheated sample was raised to 700 °C at a rate of 5 °C / min and maintained at this temperature for 5 h to promote the stabilization of the layered structure and the anchoring of the surface modification.
[0125] C) Cooling process:
[0126] After sintering, the sample was allowed to cool naturally to room temperature in the furnace, and the cooling rate was controlled at about 5 °C / min to prevent material cracks or structural damage caused by rapid cooling.
[0127] The SEM, EDS, and TEM images of the electrode after La ion embedding and sintering are shown in Figure 2. Figure 3 , 4 shown. Figure 3 The SEM and EDS images of the electrode after sintering after La ions are embedded. 1 shows the SEM image of the electrode after La ions are embedded and sintered; 2 shows the distribution of Ni elements in the EDS image, and 3 shows the distribution of La elements in the EDS image. It can be seen that the layered sodium hydroxide is sintered into a thin shell, and the La ions are fixed in this thin shell at the same time.
[0128] Figure 4 This is a TEM image of the electrode after sintering after La ion embedding. It can be seen that the electrode forms a core-shell structure after sintering, where 1 shows the inner core of the electrode, and 2 shows the outer shell formed after the layered sodium hydroxide on the surface of the electrode is pre-embedded and sintered.
[0129] Step 5: Performance Evaluation:
[0130] A) Material Characterization
[0131] Morphology observation: Scanning electron microscopy (SEM) was used to evaluate changes in the surface morphology of the material to ensure that no adverse structural changes were caused.
[0132] Surface analysis: The treated LiCoO2 surface was analyzed using Energy Dispersive X-ray Spectroscopy (EDS) to confirm the successful introduction of the target elements and their chemical state.
[0133] B) Performance Evaluation:
[0134] The test was performed using a three-electrode system, with the electrode prepared in this example as the working electrode, the mercuric oxide electrode as the reference electrode, and the platinum wire electrode as the counter electrode.
[0135] The test was carried out in a 1M KOH aqueous solution. The electrolyte was fully saturated with oxygen before the test to ensure that the oxygen concentration in the electrolyte was constant during the test.
[0136] Linear Sweep Voltammetry (LSV) Test:
[0137] LSV tests were performed to evaluate the oxygen evolution reaction (OER) activity of the materials at a scan rate of 5 mV / s in the range of 0 V to 0.8 V vs. mercuric oxide.
[0138] Electrode performance test LSV curve Figure 5 As shown. It can be seen that after the ion embedding and sintering process, the electrode performance is greatly improved.
[0139] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing an efficient and stable electrode material, characterized in that: The following steps are involved: S1: pre-treating the nickel mesh substrate to remove surface impurities; S2: preparing an electroplating solution containing a nickel source and a pore former, and adjusting the pH value thereof to a range suitable for depositing layered nickel hydroxide; S3: using the pretreated substrate as a cathode, generating a layered nickel hydroxide layer on the substrate surface by electrodeposition; S4: using an ion embedding method to allow ions to enter the layered nickel hydroxide layer, wherein the ion embedding method includes an immersion embedding method or an electrochemical embedding method; S5: The ion-embedded material is sintered in a nitrogen atmosphere, and after cooling, post-processed to obtain a highly efficient and stable electrode material.
2. The method for preparing a highly efficient and stable electrode material according to claim 1, characterized in that: In S1, the pretreatment step includes ultrasonic cleaning in dilute hydrochloric acid, deionized water and anhydrous ethanol in sequence, and then natural drying.
3. The method for preparing a highly efficient and stable electrode material according to claim 1, characterized in that: In S2, the nickel source is one of nickel sulfate, nickel nitrate and nickel chloride, the pore-forming agent is ammonium chloride, the concentration of nickel sulfate in the electroplating solution is 0.1M to 1M, the concentration of ammonium chloride in the electroplating solution is 0.5M to 4M, and the pH value of the electroplating solution is adjusted to 10 to 12.
4. The method for preparing a highly efficient and stable electrode material according to claim 1, characterized in that: In S3, during the electrodeposition process, the current density was 0.1A / cm 2 ~2A / cm 2 The electrodeposition time is 5 to 30 minutes and the temperature is 20°C to 60°C.
5. The method for preparing a highly efficient and stable electrode material according to claim 1, characterized in that: In S4, the immersion embedding method comprises the following steps: Select an ion source and prepare a soaking solution with a concentration of 0.01M to 0.1M, and adjust the pH value of the solution; The electrode after electrodeposition is completely immersed in the soaking solution, and the soaking time is controlled to be 0.1 to 100 hours under stirring conditions, and the temperature is room temperature to 80° C.; After soaking, take out the electrode, rinse it with deionized water and dry it naturally.
6. The method for preparing a highly efficient and stable electrode material according to claim 1, characterized in that: In S4, the electrochemical embedding method comprises: Select an ion source and prepare an electrolyte with a concentration of 0.01M to 0.1M, and adjust the pH value of the solution; The electrode after electrodeposition is completely immersed in the electrolyte, and a circulating current is applied to perform electrochemical cycling, wherein the cycle time is 10 min to 90 min, the number of cycles is 10 to 100 times, and the temperature is room temperature to 80° C.; After the cycle was completed, the electrode was removed, rinsed with deionized water and dried naturally.
7. The method for preparing a highly efficient and stable electrode material according to claim 5 or 6, characterized in that: In S4, the precipitation or decomposition of ions is avoided by adjusting the solution pH.
8. The method for preparing a highly efficient and stable electrode material according to claim 1, characterized in that: In S5, the sintering temperature is 500°C to 1000°C, the sintering time is 3 to 12 hours, and the heating rate and cooling rate during sintering are both 5°C / min.
9. The method for preparing a highly efficient and stable electrode material according to claim 1, characterized in that: In S4, during the ion embedding process, the ions include one or more of lanthanum ions, cobalt ions, and iron ions.
10. A method for preparing a highly efficient and stable electrode material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lanthanum-doped nickel-cobalt layered double hydroxide nano core-shell structure catalytic material as well as preparation method and application thereof
CN115094436A
Nickel-cerium composite oxide / nickel net electrode and preparation method and application thereof
CN117661015A
Alkaline electrolyzed water catalyst as well as preparation method and application thereof
CN118127547A
Manufacture of nickel positive electrode plate for alkaline storage battery
JP1997274913A
Cited By
Preparation method and application of fluorine-modified nickel-based titanium black composite anode material
CN121158901A